2022
DOI: 10.35848/1882-0786/ac79a1
|View full text |Cite
|
Sign up to set email alerts
|

Weak metastability of Al x Ga1−x N (x = 13/24, 15/24, 17/24) shown by analyzing AlGaN grown on AlN with dense macrosteps

Abstract: Energy-dispersive X-ray signals calibrated by Rutherford backscattering indicated the generation of Al13/24Ga11/24N in Ga-rich stripes in a nonflat Al0.58Ga0.42N layer. Also, the CL peak wavelengths of ~259 and 272 nm also showed the generation of Al15/24Ga9/24N and Al13/24Ga11/24N in Al-rich zones and Ga-rich stripes, respectively. The wavelength of a strong CL peak at ~246 nm, which was observed from the Al0.7Ga0.3N layer in our previous study, is also considered to correspond to the near-band-emission wavel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Our recent analytical studies on AlGaN layers with dense macrosteps revealed the generation of metastable Al n/12 Ga 1−n/12 N (n is an integer from 2 to 10) along macrostep edgelines. Results from our previous works indicated that the atomic configurations of Al n/12 Ga 1−n/12 N should have 2 or fewer monolayer (ML) configurations [31][32][33][34][35][36][37][38]. Hereafter, n ML, represents the periodicity of the structure in the c[0001] direction, where n is the number of atomic layers in a unit cell.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent analytical studies on AlGaN layers with dense macrosteps revealed the generation of metastable Al n/12 Ga 1−n/12 N (n is an integer from 2 to 10) along macrostep edgelines. Results from our previous works indicated that the atomic configurations of Al n/12 Ga 1−n/12 N should have 2 or fewer monolayer (ML) configurations [31][32][33][34][35][36][37][38]. Hereafter, n ML, represents the periodicity of the structure in the c[0001] direction, where n is the number of atomic layers in a unit cell.…”
Section: Introductionmentioning
confidence: 99%
“…12,19,20 In the literature, the AlGaN DA formation in spontaneous or controlled growth mode has been studied for standard c-oriented surfaces but few groups have reported on semi-polar or nonpolar AlGaN DA and those that have only worked on spontaneous formation. 4,7,21 However, non-polar surfaces offer an alternative to c-plane growth for future UV-LEDs with enhanced recombination rate and no quantum confined Stark effect. [22][23][24] Recently, non-polar UV emitters have been developed using lithography-free AlN nanorods 25 , hybrid top down/bottom-up process for AlN nanorods growth 26,27 , non-polar AlGaN microfins 28 , InAlNbased microtubes 29 or dislocation-free GaN nano/microwires [30][31][32] to overcome the high cost of non-polar substrates.…”
mentioning
confidence: 99%